Identifikasi Karakteristik Fisika dan Kimia Tanah Sawah Pasang Surut di SP8 Desa Tanjung Buka: Identification of Physical and Chemical Characteristics of Tidal Paddy Soil at SP8 Tanjung Buka Village - Ipung Suryanta; Fatmatul Arifah; Rina Lesmana (Universitas Hasanuddin, 2026)
This study aims to identify the physical and chemical soil characteristics of tidal swamp rice fields managed by the Makmur SP8 Farmer Group in Tanjung Buka Village, Tanjung Palas Tengah District. The research was conducted from June to July 2025 using a descriptive method with a random sampling technique. The analyzed physical parameters included soil texture, color, porosity, permeability, and moisture, while the chemical properties encompassed pH, organic Carbon (C-org), total Nitrogen (N), available Phosphorus (P), Potassium (K), Cation Exchange Capacity (CEC), and salinity. The results indicated that soil physical properties, particularly texture, porosity, and permeability, are optimal for rice cultivation, although soil color reflects the influence of tidal redox (reduction-oxidation) processes, and soil moisture was found to be less than ideal in specific locations. In contrast, soil chemical properties represent the primary constraint, characterized by acidic soil reactions (pH 4.86–5.30) and low concentrations of organic C, total N, available P, K, and CEC, while salinity levels remained within normal limits. These chemical conditions potentially restrict nutrient availability and rice productivity. Therefore, soil fertility improvement strategies should focus on enhancing organic matter, liming, and implementing balanced fertilization to support the sustainable production of tidal swamp rice.